Subcutaneous Vulvar Flap Viability Evaluation With Near-Infrared Probe and Indocyanine Green for Vulvar Cancer Reconstructive Surgery: A Feasible Technique - Capozzi, Vito Andrea; Monfardini, Luciano; Sozzi, Giulio; Armano, Giulia; Rosati, Andrea; Gueli Alletti, Salvatore; Cosentino, Francesco; Ercoli, Alfredo; Cianci, Stefano; Berretta, Roberto (Frontiers in Surgery, 2021)
Introduction: Vulvar cancer is a rare condition affecting older women and accounts for 3-5% of all gynecological cancers. Primary surgical treatment involves the removal of a large amount of tissue for which reconstructive surgery is often necessary with a high rate of postoperative complications. Despite several techniques for the evaluation of vulvar flap viability have been proposed, many methods cannot be performed during surgery and require expensive devices often missing in a gynecological clinic. This study aims to verify the feasibility and the safety of the vulvar flap viability evaluation through a near-infrared endoscopic probe and Indocyanine green (ICG) tracer in a small group of patients and to evaluate long-term vulvar flap outcomes. Methods: Patients with primary vulvar cancer who required surgical treatment and subsequent vulvar flap reconstructive surgery were prospectively included in the study. A 25 mg ICG vial diluted in 20 milliliters of saline solution was intravenously infused before closing the skin edges of the flaps. All patients were given 0.2 mg/kg body weight of intravenous ICG. After 10-15 minutes, a near-infrared endoscopic probe was used to evaluate the vulvar flap viability. Results: Of the 18 patients who underwent radical vulvectomy for vulvar cancer during the study period, 15 were included in the analysis. All packaged surgical flaps showed tracer uptake on the surgical margin. No intro-operative complications were recorded neither surgery-related nor to dye infusion. No surgical infection, dehiscence, or necrosis was recorded. Conclusions: Vulvar flap viability assessment using Indocyanine green and a laparoscopic infrared probe is a feasible method. All cases included in the analysis showed a dye uptake on the surgical edge of the flap. Further prospective studies are needed to confirm the method in clinical practice and to evaluate its superiority over simple subjective clinical evaluation.